CEO attributes and firm performance: Evidence from companies listed on Ho Chi Minh Stock Exchange - Dzung Viet Nguyen; Ngan Hoang-Kim Nguyen; Tien Thuy Dinh (Cogent Economics & Finance, 2023)
This study conducted on HOSE-listed companies for the period 2016-2020 examines the influence of chief executive officer (CEO) attributes on company performance. The System GMM methodology is applied to estimate and test dynamic panel data models. We investigate a fairly large number of CEO attributes including four socio-demographic and five corporate governance-related ones. For the socio-demographic attributes, the results indicate that female gender, below postgraduate education, domestic nationality and older age are the CEO traits that contribute to improve firm performance. With regard to the corporate governance-related attributes, this study provides statistical evidence that shorter CEO tenure, CEO-chairman duality, founder CEO, insider CEO and lower CEO ownership are the characteristics that enhance firm performance. The findings may offer valuable insights to shareholders when they expect to recruit the most qualified CEO to serve their benefits and increase their company performance.
Keywords: 330; CEO attributes; corporate governance; firm performance; HOSE-listed companies; Vietnam